Smart Working and Remote Working: Innovation within European Union - Massimiliano Ruzzeddu (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
Alongside the drastic closure of many production sectors, the Covid19 emergency has forced a wide range of businesses to reorganize using the possibilities offered by ICT. Private and, surprisingly, even public sectors have organized themselves with considerable speed, sometimes even circumventing certain legal constraints, to ensure the maximum possible performance through remote working. Employees, teachers, lawyers, consultants and other professionals have, in fact, begun to coordinate online work among colleagues, users and customers, so as to be able to guarantee, at least in part, the performance necessary for their work. The purpose of this study, on the other hand, is to examine the remote working phenomenon which, although easier to identify, implies very significant social changes, which in turn imply rather complex epistemic problems.Namely, I will try to respond the following Research Questions: a) how much is the phenomenon widespread across EU? b) is the introduction of RW only a consequence of the pandemic, or does it depend on a propensity for innovation?